A new genus and species of freshwater crab (Decapoda, Pseudothelphusidae) from the Tapajós River, a southern tributary of the Amazon River in Brazil - Magalhães, Célio (Crustaceana, 2017)
A new genus and species of pseudothelphusid crab of the tribe Kingsleyini Ortmann, 1897, from the Tapajós River, a southern tributary of the Amazon River basin in the state of Pará, Brazil, is described and illustrated. Michaelthelphusa tuerkayi gen. et sp. nov. is characterized by the male first gonopod possessing marginal and lateral sutures fused at the distal third of the stem and the merged portion strongly twisted towards the lateral side; an apex transversally expanded along caudal-cephalic axis, with a well-developed, but low, somewhat depressed, apical plate; apical plate with spine-like outgrowth cross overlapping the spine-like projection of the mesial process. Moreover, the relationship of the new genus and species with other pseudothelphusid genera from the Amazon basin is discussed. © Copyright 2017 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: Crab; Morphology; Neotropical Region; New Genus; New Record; Taxonomy; Tributary; Amazon Basin; Tapajos River; Brachyura; Crustacea; Decapoda (crustacea); Kingsleyini; Pseudothelphusidae